Heavy Chiral Fermions and Dark Matter - Johan Alwall; Jusak Tandean (Advances in High Energy Physics)
Dark matter presents perhaps one of the most compelling direct indications of new physics beyond the standard model with three generations of fermions. In this paper, we survey several scenarios for dark matter in association with a fourth generation of chiral matter. The surveyed scenarios include stable heavy neutrino dark matter, composite dark matter consisting of stable heavy quarks, heavy quarks as mediators between the dark and visible sectors, and the four-generation standard model with the minimal addition of a stable real scalar field. We discuss the basic properties of the models, direct search constraints on their dark matter, and their collider phenomenology, as well as the possible effects of dark matter on the searches for a Higgs boson in the presence of four generations. We also comment on the potential implication of the recent observation of a Higgs-like new particle at the LHC.